Development of Four Tier Multiple Choice Diagnostic Tests to Know Students' Misconceptions in Science Learning - Juliani Juliani; Yusrizal Yusrizal; Ismul Huda (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the quality of the four-tier multiple choice diagnostic test instrument and the level of students' misconceptions. The research method used is research and development (R&D). The population in this study were class IX students at MTs Negeri 2 Aceh Besar. The number of samples consisted of 112 students in group A, each class consisted of 16 students during the Covid-19 pandemic. The research instrument used is a four-tier multiple choice diagnostic test. The data analysis technique in the validation test obtained a high and valid Aiken's V coefficient value. The results in terms of item analysis quantitatively obtained the validity of the questions 75% valid and 15% invalid, the reliability test was 0.786 high category. The level of difficulty of the questions includes 85% too easy questions and 15% easy questions. The differentiating power of the questions obtained in each category is 5% very good, 55% good, 20% sufficient and 20% bad. The results of the students' level of misconceptions using the four-tier multiple choice diagnostic test were obtained from the results of the overall analysis of students with an average of 21.76% and the results of the item analysis showed that the highest student misconceptions were in question number five with a percentage of 11.6% and the lowest found in question number four with a percentage of 0%.